Pencegahan Serangan Bubuk Dinoderus minutus Farb. pada Bambu Lapis dan Kayu Lapis The Prevention of the Powder Post Beetle Dinoderus Minutus Farb. Infestation on Plybamboo and Plywood - Jasni Jasni; I M Sulastiningsih (Jurnal Ilmu dan Teknologi Kayu Tropis, 2005)
Bamboo and wood are essential natural resources in Indonesia. Both natural resources can be made for plybamboo and plywood respectively. However, bamboo and wood are very susceptible to powder post beetle infestation. To cope with the infestation, a preservative treatment is applied. The permethrin preservative with active ingredient of 36.8 % was mixed in the urea formaldehyde glue, and the concentrations used were 0%; 0.5%; 1.0% and 1.5% based on urea formaldehyde weight (or 0 g/m3, 450 g/m3, 900 g/m3 and 1,350 g/m3 based on plybamboo or plywood volume). The bamboo species, Gigantochloa apus Kurz. and the wood species, Anthocephalus cadamba Miq. were used respectively. The durability of plybamboo and plywood were tested to the powder post beetle Dinoderus minutus Farb.The results revealed that the higher the preservative concentration the higher the mortality of powder post beetle, the lower the rate of beetle infestation for both on plybamboo and plywood. The addition of permethrin in the urea formaldehyde glue at the minimum level of 0.5% (450 g/m3) was effective to prevent the infestation of powder post beetle Dinoderus minutus Farb on plybamboo and plywood